Immediate and short‐term effects of real‐time knee adduction moment feedback on the peak and cumulative knee load during walking. Issue 1 (10th August 2017) - Jackson, Brennan; Gordon, Keith E.; Chang, Alison H.
ABSTRACT: The peak external knee adduction moment (pKAM), KAM impulse, and peak knee flexion moment (pKFM) during gait are important loading variables in medial tibiofemoral osteoarthritis. We evaluated the effects of gait modification, using real‐time pKAM visual feedback, on pKAM, KAM impulse, and pKFM; and whether participants could maintain the KAM‐reducing gait after feedback removal. Eleven healthy individuals performed a series of walking trials on a split‐belt instrumented treadmill under four conditions of Baseline, Feedback, No Feedback Early, and No Feedback Late. Guided by real‐time feedback of pKAM, they modified their gait patterns to lower pKAM by 20%. Three‐dimensional joint kinematics/kinetics during each walking condition were recorded by a 12‐camera motion capture system and the instrumented treadmill. Change in each knee loading parameter from baseline across conditions was assessed using one‐way repeated‐measures analysis‐of‐variances. In the feedback limb, successful 20% reductions from baseline in pKAM and KAM impulse were achieved across all three conditions. There was a trend for concomitant pKFM increases, partially attenuating the beneficial effects of pKAM reduction. A carry‐over effect of KAM reduction in the non‐feedback limb was noted. The altered gait patterns were participant‐specific and multi‐modal; each participant reported a combination of two to three gait modification strategies used for pKAM reduction. Toe‐in and medial foot contact were the most reported strategies. The findings support the real‐time pKAM visual feedback as a tool for individualized gait modification to reduce knee load. Future studies to evaluate its effectiveness in persons with or at risk for medial knee osteoarthritis is warranted. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:397–404, 2018. Abstract : Guided by real‐time visual feedback of the peak external knee adduction moment (KAM) of the right limb during instrumented‐treadmill walking, participants learned to modify their gait patterns and reduced the peak KAM and stance‐phase KAM impulse (cumulative load) by 20%. A carry‐over effect of KAM reduction in the left limb was noted. The altered gait patterns were participant‐specific and multi‐modal. The findings support the real‐time peak KAM visual feedback as a tool for individualized gait modification to reduce knee load.